The significance of the immunohistochemical method in diagnosing atypical endometrial polyps as manifestations of localized hyperplasia - O.V. Poslavska; D.A. Khaskhachykh; I.S. Shponka; V.O. Potapov (Medičnì Perspektivi)
The article explores the role of immunohistochemical methods in diagnosing atypical endometrial polyps as manifestations of localized hyperplasia. Endometrial polyps are a widespread pathology among women of reproductive age, frequently accompanied by hyperplastic tissue changes. The aim of the work was to investigate the expression of diagnostic markers in endometrial polyps, which may be manifestations of local endometrial hyperplasia, with the aim of improving differential diagnosis in their atypia.. The research material consisted of histological samples from 37 patients aged 38 to 52 with abnormal uterine bleeding, treated at a clinical hospital in Dnipro. The methods included histological tissue analysis, immunohistochemical studies using a panel of antibodies, and statistical data analysis. Antibodies targeting markers such as ER, PR, PAX-2, PAX-8, PTEN, Ki-67, p16, and p53 were used to evaluate proliferative activity and the degree of tissue atypia. The results showed that polyps associated with atypical hyperplasia are characterized by complex morphological changes, including abnormal glandular architecture, stromal atypia, and increased mitotic activity in both glandular and stromal components. Epithelial differentiation of tubal, mucinous, or mixed types was frequently observed. More than half of the cases exhibited partial atypical changes, while diffuse atypia was noted in fewer instances. The control group of glandular-fibrous polyps with hyperplasia without atypia demonstrated low mitotic activity and no cellular atypia. Immunohistochemical studies confirmed the high sensitivity of markers in identifying pathological changes, particularly in diagnostically challenging cases. The conclusions emphasize that immunohistochemistry is an effective tool for detecting endometrial atypia, and the diagnosis of atypical polyps should be based on a comprehensive analysis of morphological and molecular changes. Polyps associated with hyperplasia and atypia require further observation due to the risk of recurrence and potential malignant transformation. Utilizing markers such as PAX-2, PTEN, and Ki-67 enhances diagnostic accuracy. Additional studies are needed to develop more reliable risk stratification models.